Design of Lighting System for Surface Mine Projects - Mangalpady Aruna; Sunil M Jaralikar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Indian mining illumination standard is based on incident light without mentioning about uniformity ratio, but International Commission on Illumination (CIE), Austria insists uniformity ratio. In a mine with low surface reflectance, the surrounding illumination level is lower than the minimum lighting standard as specified by various regulatory bodies. The surface brightness further reduces in wet surface condition, and results in poor visibility. In the present study, design was made both in mineral and overburden benches based on the minimum acceptable reflected light and the reflected uniformity ratio. For the purpose of comparison of various types of lighting systems, a stretch of 1.0 km long haul road was considered. The design was attempted with five different types of luminaries. Lamp mounting heights were varied at five steps, namely 8, 10, 12, 14 and 16 m. Design under wet condition incurs an excess cost 9.4 % for mineral bench and 50 % for overburden bench haul roads. Designing under wet surface condition ensures the minimum light level even under the worst condition of surface reflectivity, with marginal increase in cost.